Comparative study on the compressive performance of honeycomb structures fabricated by stereo lithography apparatus - Liu Bomin; Cao Shengbin; Zheng Jiayi; Cao Fenghua; Yu Mingliang (AUTEX Research Journal, 2025)
To investigate the influence of materials on the surface morphology and compressive performance of honeycomb structural components prepared by stereo lithography apparatus (SLA) technology, three typical materials, namely Dutch State Mines (DSM) 8000, Somos® Taurus, and FS 3400GF (Glass Bead Filled Nylon Powder), were selected as raw materials for printing honeycomb structure via SLA. FS 3400GF can withstand a maximum compression force of 14.1 kN in vertical compression, while it is 10.1 kN for DSM 8000 and 5.8 kN for Somos® Taurus, indicating that FS 3400GF bears significantly higher vertical pressure. The maximum force bore by FS 3400GF under lateral compression is 0.47 kN, DSM 8000 is 0.56 kN, and Somos® Taurus is 0.17 kN, suggesting that the lateral compression failure is highly likely to occur. The mechanical compression failure reveals the physical properties of honeycomb structures and provides an experimental support for expanding the potential functional application of honeycomb structures in additive manufacturing.